Night kites - Kerr, M. E. (New York HarperCollins, 1986)
Seventeen-year-old Erick's comfortable and well-ordered life begins to fall apart when he is forced to keep two secrets: the identity of his new girlfriend and the nature of his brother's debilitating disease.
"A Charlotte Zolotow book."
Keywords: Family problems -- Fiction; Brothers -- Fiction; AIDS (Disease) -- Fiction